2014
DOI: 10.1371/journal.pone.0098739
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Carriage Prevalence in Nepal: Evaluation of a Method for Delayed Transport of Samples from Remote Regions and Implications for Vaccine Implementation

Abstract: BackgroundPneumococcal disease is a significant cause of morbidity and mortality in young children in Nepal, and currently available pneumococcal conjugate vaccines offer moderate coverage of invasive disease isolates.MethodsA prevalence study of children aged 1.5 to 24 months in urban and rural Nepal was conducted. In the urban group, nasopharyngeal swabs (NPS) were transported using silica desiccant packages (SDP) with delayed processing (2 weeks), or skim-milk-tryptone-glucose-glycerin (STGG) with immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…We previously reported a pneumococcal carriage prevalence of 64% in children aged 12-24 months old in the Bandung region, suggesting that carriage rates stabilize after 12 months in this population (Dunne et al, 2018). Carriage prevalence tended to be higher in infants living in semi-rural areas than in urban residents, as observed in some, but not all, other studies (Hanieh et al, 2014;Nisar et al, 2018). Previously, we did not observe differences in pneumococcal carriage between urban and semi-rural Indonesian children aged 12-24 months, suggesting that differences diminish with age (Fadlyana et al, 2018).…”
Section: Discussionsupporting
confidence: 51%
“…We previously reported a pneumococcal carriage prevalence of 64% in children aged 12-24 months old in the Bandung region, suggesting that carriage rates stabilize after 12 months in this population (Dunne et al, 2018). Carriage prevalence tended to be higher in infants living in semi-rural areas than in urban residents, as observed in some, but not all, other studies (Hanieh et al, 2014;Nisar et al, 2018). Previously, we did not observe differences in pneumococcal carriage between urban and semi-rural Indonesian children aged 12-24 months, suggesting that differences diminish with age (Fadlyana et al, 2018).…”
Section: Discussionsupporting
confidence: 51%
“…The majority of epidemiological studies that have been conducted in developed countries have shown that the pneumococcal serotypes and STs that circulate in carriage and disease are broadly similar across different populations [9], In contrast, recent epidemiological studies in places like Bolivia, Kenya, Malaysia and Nepal, which characterised pneumococci only by traditional MLST, demonstrated that whilst the most prevalent serotypes tend to be the same as those in the developed world, the diversity of STs/CCs was greater [16-19], Importantly, safe and effective pneumococcal conjugate vaccines (PCVs) are now used in many countries, but they significantly disrupt the pneumococcal population structure and this can have unpredictable consequences [3, 20-21], Therefore, characterising the pre-and post-PCV pneumococcal population structure is essential in order to identify the changes that occur. Whilst traditional MLST is still highly useful in that regard and will remain the genotyping method of choice in many parts of the world for some time, genomics provides a higher discriminatory level of resolution to such analyses and should be employed wherever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Equal numbers of participants were to be recruited from each of three age groups: 6 weeks to 5 months + 29 days, 6 months to 11 months + 29 days and 12 months to 24 months. In a prior study of pneumococcal carriage in Nepal using conventional microbiological methods over 40 serotypes were detected with the maximum prevalence of a single serotype being 8·5% [ 24 ]. In that study the sample size of 600 was based on the feasibility of recruitment logistics as well as the precision of the results obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were excluded if they had documented evidence of previous pneumococcal vaccination, recent antibiotic treatment, or had a febrile illness/temperature of more than 38ºC. Due to the higher prevalence of nasopharyngeal carriage observed in rural compared to urban populations in Nepal [ 24 ], only children who resided within the urbanised setting of the Kathmandu Valley were included. Demographic and medical data were collected and participants swabbed by trained research staff according to WHO guidelines [ 15 ].…”
Section: Methodsmentioning
confidence: 99%